Tailored solution-based N-heterotriangulene thin films: unravelling the self-assembly - Hawly, Tim; Streller, Fabian; Johnson, Manuel; Miguez-Lago, Sandra; Hammer, Natalie; Hampel, Frank; Vivod, Dustin; Zahn, Dirk; Kivala, Milan; Branscheid, Robert; Spiecker, Erdmann; Fink, Rainer H. (ChemPhysChem, 2021)
The ability of a series of bridged triarylamines, so-called N-heterotriangulenes, to form multilayer-type 2D-extended films via a solution-based processing method was examined using complementary microscopic techniques. We found that the long-range order, crystallinity, and layer thickness decisively depend on the nature of the substituents attached to the polycyclic backbone. Owing to their flat core unit, compounds exhibiting a carbonyl unit at the bridge position provide a superior building block as compared to thioketone-bridged derivatives. In addition, nature and length of the peripheral substituents affect the orientation of the aromatic core unit within highly crystalline films. Hence, our results stress the significance of a suitable molecular framework and provide deeper understanding of structure formation in 2D-confined surroundings for such compounds.
First published:
Gesehen am 20.09.2022